Temporal variations in fumarole gas chemistry at Poás volcano, Costa Rica - Fischer, Tobias P. (2015)
We report the chemical and isotopic composition of fumarole gas discharges collected at Poás Volcano, Costa Rica from 2001 to 2014, covering a period during which the volcano experienced a series of phreatic eruptions (March 2006 to October 2014). The relative abundances of Poás C–S–H–O gas species are controlled by reactions involving the SO2–H2S and So–SO2 gas buffers indicating magmatic temperatures of up to 800 °C. Although fumarole outlet temperatures are < 120 °C for most samples, SO2 is the dominant sulfur gas and HCl contents are relatively high. Gas compositional changes within the magma-lake-hydrothermal system likely result from a combination of several processes, including: 1) The injection of new and undegassed magma in late 2000–early 2001, 2) the heating of the hydrothermal system, accompanied by gas pressure build-up, and 3) hydrofracturing through 2006. These processes culminated in the phreatic eruptions of 2006 and 2008. Since 2005 the lake level has declined and is now (January 2014) at the lowest level (10 m) since the last periods that it dried out completely (April 1984 and April 1994). The most recent data of 2014 show high level of degassing from the dome fumaroles and the release of HCl-rich and CO2-poor gases implies that the magma injected in late 2000 continues to supply volatiles. Our data show that time series sampling of fumarole gases provides important insights to better understand magmatic and hydrothermal processes at active volcanoes and also to potentially forecast phreatic eruptions.